Implementation of basic tools for a laboratory with RFID technology - García Zapata, Teonila (2012)
With the implementation of the basic equipment of radio frequency identification technology (RFID) 1, are better able to train teachers in the specialty of Industrial Engineering and Engineering Textiles and clothing, and their undergraduate and graduate Industrial Engineering faculty. With this new, modern laboratory technology is among the best and modern facilities of public and private universities. By introducing the curriculum laboratory identification technology (RFID), may enable students and disseminate this training to the employees of companies, seeking to improve the teaching-learning: reducing inventories, tracking of orders , reducing operating costs and labor, better use of reusable assets of the company (pellets, cargo trucks, etc.).